Analisa Pengaruh Minat Konsumen Berkunjung Terhadap Keputusan Membeli di Cafe Strawberry (Jurnal Ilmiah Pariwisata, 2016)
Café first appeared in the western region, the most common café term found in the French country which was then adopted by the city town in England at the end of the 19th century. The term café comes from the word coffe which means coffee. Café is a suitable place to relax and release fatigue, and meet with relatives or friends. Café strawberry is one of the unique restaurant. This restaurant is located in a very strategic area that is located at Jalan Gandaria 1 No.75 South Jakarta. Consumers as individuals who choose a product they want are influenced by many factors, where they differ from one to another. This difference that affects consumer interest and behavior in making decisions to buy the products that they want. The purpose of this study is to determine the influence of consumer decision to buy at the strawberry café . Using descriptive methods to describe the phenomena studied systematically, factually, and accurately. This research uses purposive sampling technique. Collect primary data by observation and interview with 67 visitors who come to strawberry cafe. Factors studied were emotional factors (3.99), interest in visiting (3.78), to relax (4.77), due to hunger (2.80), social motive factors (3.34), emotional factors (3.7). The results of this study can be seen that the dominant factor is consumer interest and this will increase consumer decision to buy.